The Integration Of Relationship Building Skills In Microteaching Sessions: A Social Emotional Learning (SEL) Perspective - Affny Muslihha; Hardianti (JIBEMA: Jurnal Ilmu Bisnis, Ekonomi, Manajemen, dan Akuntansi, 2026)
Recent studies have highlighted the importance of microteaching in developing pedagogical competency among prospective teachers. However, limited research has examined the relational dimension of teaching in microteaching practices, particularly from a Social-Emotional Learning (SEL) perspective. Therefore, this study examines the integration of relationship-building skills during microteaching sessions. This study aims to examine how relationship-building skills based on the SEL framework are demonstrated and integrated in prospective English language teachers' microteaching practices. This study employed a descriptive qualitative design utilizing directed qualitative content analysis. Participants consisted of ten prospective teachers enrolled in a microteaching course at a private university in West Jakarta during the 2024/2025 academic year. Data were collected through video recordings of teaching performances, semi-structured interviews, lesson plans, and peer feedback documents. Data were analyzed using deductive-inductive content analysis guided by the CASEL relationship skills framework. Findings indicate that relationship-building skills were present but demonstrated unevenly among participants. Clear instructional communication, supportive feedback, and facilitative leadership were most frequently demonstrated, particularly during the instructional delivery and feedback stages. However, higher-order relational competencies such as constructive conflict resolution, advocacy for justice, and resistance to negative social pressure are rarely observed. These findings contribute to the understanding of relational competencies in teacher education and demonstrate the need to explicitly integrate SEL-based relationship-building skills into microteaching assessments and teacher education curricula.